Efekty funkcjonowania centrów logistycznych w kontekście strategii zrównoważonego rozwoju transportu - Miklińska, Joanna (Effects of Functioning of the Logistic Centers in the Strategy of Sustainable Development of Transport, 2008)
The article is an attempt to interpret the multidimensional effects of functioning of the logistic centers from the view point of strategy of sustainable development of transport. The effects (socio-economical and environmental) could be arguments for the construction and development of the logistic centres as well as involving the public site in these activities.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 154-166